Criminal Protection of Human Genome “Human Gene Editing as a Model” - Sahar Fouad Majeed Al- Najar, (Journal of Legal Sciences, 2024)
Lawful protection of the human gene conceded a moral concern regarding the future of existence human. After the discovery of the human genetic map, scientific experiments and research related to the human gene increased, negative applications of genetic engineering  in particular that violate essential human rights,  the right to human dignity to be specific. These practices represent actual challenges to the existence and diversity of current and future generations. Therefore, the presence of legal rules at the domestic and global levels is an absolute necessity to prohibit these threats and determine civil and criminal accountability for those who infringe any laws related to this issue.